2020
DOI: 10.1002/jbmr.4294
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Incident Vertebral Fracture Detection in Children Using Targeted Case-Finding Approaches

Abstract: Vertebral fractures are clinically important sequelae of a wide array of pediatric diseases. In this study, we examined the accuracy of case-finding strategies for detecting incident vertebral fractures (IVF) over 2 years in glucocorticoid-treated children (n = 343) with leukemia, rheumatic disorders, or nephrotic syndrome. Two clinical situations were addressed: the prevalent vertebral fracture (PVF) scenario (when baseline PVF status was known), which assessed the utility of PVF and low lumbar spine bone min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In the absence of high energy trauma or falls from a significant height, these fracture sites also indicate underlying bone fragility. 53,54 Furthermore, vertebral fractures may be asymptomatic, and their incidence is likely underestimated. Two prior studies have examined vertebral fractures in children with nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of high energy trauma or falls from a significant height, these fracture sites also indicate underlying bone fragility. 53,54 Furthermore, vertebral fractures may be asymptomatic, and their incidence is likely underestimated. Two prior studies have examined vertebral fractures in children with nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on these fracture sites in particular because they are rare but associated with significant morbidity. In the absence of high energy trauma or falls from a significant height, these fracture sites also indicate underlying bone fragility 53 , 54 . Furthermore, vertebral fractures may be asymptomatic, and their incidence is likely underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Left-hand and wrist radiographs were obtained to determine bone age ( 20 ). Lumbar spine bone mineral density (LS BMD) was assessed by dual-energy x-ray absorptiometry using either Hologic (QDR 4500, 3 centers; Discovery, 2 centers; Delphi, 1 center; Hologic, Inc., Marlborough, MA, USA) or Lunar (Prodigy, 4 centers; GE Healthcare, Chicago, IL, USA) systems at baseline and every 6 months in the first 4 years and annually thereafter, with details about the scan mode, cross-calibration, and analysis software programs described previously ( 21 ). Raw LS BMD results were converted to Hologic units, and age- and sex-matched Z-scores were generated using the Hologic 12.3 normative database ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…To date the onset of osteopathologies in survivors of childhood malignancies is not yet well characterized. Recent studies in ALL indicate that impaired bone health may be observed as early as at the time of manifestation of the malignancy ( 18 , 19 ) and is present in many survivors during follow-up ( 15 ).…”
Section: Introductionmentioning
confidence: 99%